The Effect of Price and Product Quality on the Decision to Purchase Ventela Shoes in Banjarmasin City - MuhammadLukmanHusaini; HasanurArifin; RizkiMuslimHidayat; Humaidi (Magister Administrasi Bisnis ULM, 2024)
Abstract: The development of increasingly complex consumer needs and increasingly sharp market competition causes many things to influence consumer purchasing decisions for a product. This study aims to determine the effect of price and product quality partially and simultaneously on purchasing decisions. This study uses a quantitative approach with the type of explanatory research. Respondents in this study were buyers and users of Ventela shoes in the city of Banjarmasin who were taken using purposive sampling technique. So that 120 respondents who are buyers and users of Ventela shoes are obtained as research samples. The type of data used is sourced from primary data obtained from the distribution of questionnaires. Data analysis used descriptive analysis and multiple linear regression analysis. Data processing was carried out using SPSS 26 for windows computer software. The results showed that partially the price variable (X1) had a significant effect on purchasing decisions (Y) with a significant value of 0.000 <0.05, the value of t arithmetic was 3,721 > t table 1,980 and a large effect of 33.3%, product quality (X2) has a significant effect on purchasing decisions (Y) with a significant value of 0.000 <0.05, the value of t arithmetic is 5.215 > t table 1.980 and the influence is 46.7%. Simultaneously, the price variable (X1) and product quality (X2) have a significant effect on purchasing decisions (Y) with a significant value of 0.000 <0.05, F count 72.457 > F table 3.07 and a large influence of 52.5%.